The Importance of Sustainability Reports In Non-Financial Companies - Shinta Melzatia, Caturida.M.Doktoralina, Dewi Anggraini,Safira, (Jurnal Akuntansi, 2018)
The sustainability report (SR) has become a necessity for companies. Its role is crucial for the development of a company because it includes both social and environmental aspects. However, there are still companies that have not properly conducted sustainability report disclosures (SRDs). Therefore, this study aims to examine the effects of profitability, leverage and liquidity on SRDs. In particular, we explore the implications of regulations that require the disclosure of environmental and social information in non-financial companies listed on the Indonesia Stock Exchange (IDX) in 2013-2017. The sample in this study was 65 from 13 companies that met the criteria, and the study utilised the purposive sampling method. The study results found that first, profitability proxied by return on assets (ROA) did not significantly influence SRDs. Second, leverage proxied by debt to assets ratio (DAR) has a significant negative effect on SRDs, and third, the liquidity proxied by the current ratio (CR) has a significant negative effect on SRDs. The results of this study are expected to increase knowledge for readers, especially investors, so they can pay better attention to a company's social and environmental activities when investing.